2007
DOI: 10.1093/cercor/bhm046
|View full text |Cite
|
Sign up to set email alerts
|

Transient Cortical Excitation at the Onset of Visual Fixation

Abstract: Primates actively examine the visual world by rapidly shifting gaze (fixation) over the elements in a scene. Despite this fact, we typically study vision by presenting stimuli with gaze held constant. To better understand the dynamics of natural vision, we examined how the onset of visual fixation affects ongoing neuronal activity in the absence of visual stimulation. We used multiunit activity and current source density measurements to index neuronal firing patterns and underlying synaptic processes in macaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
238
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(279 citation statements)
references
References 84 publications
(127 reference statements)
37
238
4
Order By: Relevance
“…Modulation of the phase of theta may have important implications for cognition, as demonstrated in some studies of hippocampal long-term potentiation (36)(37)(38) and sensory processing (34,39). For example, neural activity in the hippocampus may be influenced by theta phase in such a way that resetting to an "ideal" phase on saccade initiation may set up the optimal conditions for plasticity, and thus memory formation.…”
Section: Resultsmentioning
confidence: 99%
“…Modulation of the phase of theta may have important implications for cognition, as demonstrated in some studies of hippocampal long-term potentiation (36)(37)(38) and sensory processing (34,39). For example, neural activity in the hippocampus may be influenced by theta phase in such a way that resetting to an "ideal" phase on saccade initiation may set up the optimal conditions for plasticity, and thus memory formation.…”
Section: Resultsmentioning
confidence: 99%
“…Periodic sampling was quantified as the correlation between the phase of prestimulus EEG oscillations and the detection of these stimuli. Electrophysiological oscillations reflect periodic variations of membrane potentials in neuronal ensembles, which are associated with variations of neural excitability (15,16,20,32). Thus, the momentary phase of ongoing oscillations at the time a stimulus is presented can influence the strength of the neural response to the stimulus (19,(33)(34)(35)(36)(37) and the speed of manual reaction times (19,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that covert shifts of attention (i.e., shifts that do not involve eye movements) were locked to oscillations in the frontal eye fields, such that each cycle of the oscillation corresponded to a distinct item. These oscillations occurred in the β frequency range (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), but the exact frequency was variable across trials and correlated with single-trial reaction times. Thus, the authors suggested that the speed of attentional shifts might be controlled by the frequency of the underlying oscillations (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, physiological beta-band coherence leads to spikes optimally timed for impact onto the spinal cord. Related analyses of ongoing or evoked phases that lead to enhancement or suppression of neuronal responses have been performed previously in other systems and frequency bands (Kruglikov and Schiff, 2003;Lakatos et al, 2007Lakatos et al, , 2008Rajkai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%